Junie B. Jones is a party animal - Park, Barbara; Brunkus, Denise (New York : Scholastic, 1997)
Lucille invites Junie B. and her friend Grace to sleep over at her very rich nanna's house, where everything is beautiful, expensive, and breakable.
K
"A Stepping Stone book."
b
b
Keywords: Grandmothers -- Fiction; Wealth -- Fiction